Application of Financial Statements of Non-Profit Organizations based on ISAK 35 at the Indonesian Methodist Church in Reinata Resort (GMI Reinata) - Delima Hutagalung; Sahala Purba (Asian Journal of Applied Business and Management, 2022)
The purpose of this study is to understand the comparison of GMI Reinata's financial statements with their financial statements sorted according to ISAK 35. This study uses a qualitative method. This study uses a descriptive analysis method by comparing the theory contained in ISAK 35 with the practice contained in GMI Reinata. The data collection technique in this study is observation. The results show that GMI Reinata's financial reports are only income and expenditure reports, so they are not in accordance with the standards that apply to ISAK 35. The conclusion of this study is that GMI Reinata has not designed its financial reporting process in accordance with ISAK 35.